Mob/oriT, a mobilizable site-specific recombination system for unmarked genetic manipulation in Bacillus thuringiensis and Bacillus cereus. Issue 1 (December 2016) - Wang, Pengxia; Zhu, Yiguang; Zhang, Yuyang; Zhang, Chunyi; Xu, Jianyi; Deng, Yun; Peng, Donghai; Ruan, Lifang; Sun, Ming
Abstract Background Bacillus thuringiensis andBacillus cereus are two important species inB. cereus group. The intensive study of these strains at the molecular level and construction of genetically modified bacteria requires the development of efficient genetic tools. To insert genes into or delete genes from bacterial chromosomes, marker-less manipulation methods were employed. Results We present a novel genetic manipulation method forB. thuringiensis andB. cereus strains that does not leave selection markers. Our approach takes advantage of the relaxase Mob02281 encoded by plasmid pBMB0228 fromBacillus thuringiensis . In addition to its mobilization function, this Mob protein can mediate recombination betweenoriT sites. The Mob02281 mobilization module was associated with a spectinomycin-resistance gene to form a Mob-Spc cassette, which was flanked by the core 24-bporiT sequences from pBMB0228. A strain in which the wild-type chromosome was replaced with the modified copy containing the Mob-Spc cassette at the target locus was obtained via homologous recombination. Thus, the spectinomycin-resistance gene can be used to screen for Mob-Spc cassette integration mutants. Recombination between the twooriT sequences mediated by Mob02281, encoded by the Mob-Spc cassette, resulted in the excision of the Mob-Spc cassette, producing the desired chromosomal alteration without introducing unwanted selection markers. We used this system to generate an in-frame deletion of a target gene inB. thuringiensis as well as a gene located in an operon ofB. cereus . Moreover, we demonstrated that this system can be used to introduce a single gene or an expression cassette of interest inB. thuringiensis . Conclusion The Mob/oriT recombination system provides an efficient method for unmarked genetic manipulation and for constructing genetically modified bacteria ofB. thuringiensis andB. cereus . Our method extends the available genetic tools forB. thuringiensis andB. cereus strains.